Characteristics and applications of magnetized water as a green technology. (10th September 2017) - Esmaeilnezhad, Ehsan; Choi, Hyoung Jin; Schaffie, Mahin; Gholizadeh, Mostafa; Ranjbar, Mohammad
Abstract: Water can be magnetized under an applied magnetic field, and some important properties of magnetized water have become useful in industries associated with its surface tension, pH, viscosity, electrical conductivity, and scale formation inhibition. The surface tension of water decreases upon the application of a magnetic field, while its pH increases. In addition, the shear viscosity of magnetized water increases and the magnetic field inhibits scale formation. This paper reviews the unique properties of magnetized water as well as its potential applications as a smart and more environmentally friendly fluid in the oil industry, e.g., as an injection fluid in enhanced oil recovery areas for producing oil.